2015
DOI: 10.1177/0021998315574754
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of kink bands and hygrothermal conditioning on tensile strength of polyarylate liquid crystal co-polymer and aramid fibers

Abstract: Translation of tensile properties from high-performance fibers to end-use fabrics is sensitive to weaving-induced filament defects and environmental exposure. In this effort, isolated and combined effects of hygrothermal exposure and curvature-induced kink bands on tensile strength of Vectran TM HT (polyarylate liquid crystal polyester fiber) and Kevlar Õ KM2 are studied. Hygrothermal conditioning was conducted at temperatures ranging from 40 C to 100 C in water for 30 days. Curvature-induced defects were crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…In general, this is much higher than compression strain for structural carbon fiber (less than 1%). However, kink-bands can also form in flexural loading when the radius of curvature exceeds a threshold value [27]. This type of failure mode may affect the resistance-strain behavior.…”
Section: Progressive Tensile Cyclic Loadingmentioning
confidence: 99%
“…In general, this is much higher than compression strain for structural carbon fiber (less than 1%). However, kink-bands can also form in flexural loading when the radius of curvature exceeds a threshold value [27]. This type of failure mode may affect the resistance-strain behavior.…”
Section: Progressive Tensile Cyclic Loadingmentioning
confidence: 99%
“…In their study, they report that KM2 fibers loaded in flexure fail in compression through the formation of kink-bands that causes fibrillation of the fiber microstructure. Obaid et al (2015) also observed micro cracking and fibrillation in Kevlar KM2 fibers and reported a 10% loss in tenacity due to kink bands.…”
Section: Introductionmentioning
confidence: 87%
“…For the case of R = 2.0 mm, the fiber undergoes reverse bending with increasing time and both top and bottom fiber surfaces are predicted to undergo compressive kinking. Based on the elastica loop experiments of Leal et al (2009) on single fibers, the fibers fibrillate under compressive kinking which leads to a reduction in tensile strength (Obaid et al, 2015). Fibrillation would also likely lead to reduction in the longitudinal shear modulus that may result in a 'string' like response shown in Fig.…”
Section: Single Fiber Fe Model Subjected To Cylindrical Impact: Flexumentioning
confidence: 99%
“…A constant 18% increase in the average failure strain due to strain rate effect is assumed for all gage lengths, as shown in Figure 11 (Weibull high rate curve). While the strain rate effects increase the tensile strength [26], multiaxial loading effects degrade the strength [28][29][30]. where L0 is the reference gage length (12.7 mm) at which the scale ε 0 = 0.044 and shape parameters m = 13.25 are determined, and P(ε, L) is the cumulative probability of failure of a gage length L at a strain level ε.…”
Section: Failure Criterionmentioning
confidence: 99%
“…A constant 18% increase in the average failure strain due to strain rate effect is assumed for all gage lengths, as shown in Figure 11 (Weibull high rate curve). While the strain rate effects increase the tensile strength [26], multiaxial loading effects degrade the strength [28][29][30]. The failure criterion developed [17] based on the analyses and validation of multiaxial quasistatic loading experiments is extended for the dynamic loading and given in Equation (3): ε 3,max (t) ε 3,fail (t) = 1 ( (3) where: where ε3,max is the maximum axial tensile strain predicted by the model, ε3,fail is the axial tensile failure strain, which is a function of the failure strain based on the Weibull model at a gage length equal to contact length (Lc), (1 − ACr), (1 − TCr), and (1 − ILSr) are the reduction factors in the respective individual deformation modes based on the maximum levels of loading in the time history.…”
Section: Failure Criterionmentioning
confidence: 99%